Academician Vladimir Ivanovich Burakovsky (1922–1994) (on the 100th anniversary of his birth) - A. A. Kurygin; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
Professor Vladimir Ivanovich Burakovsky was born on August 20, 1922 in Tiflis (Tbilisi). In 1940, Vladimir entered the Tbilisi Medical Institute. In 1947, V. I. Burakovsky was enrolled in a clinical residency at the Department of Faculty Surgery № 2 (since 1955 – Department of Surgery for Advanced Doctors № 1) Military Medical Academy named after S. M. Kirov in Leningrad. In the spring of 1960, Vladimir Ivanovich was accepted as a senior researcher at this Institute and appointed the head of the Department of Surgery of the heart and blood vessels in children. Vladimir Ivanovich was the author and co-author of more than 500 scientific papers, including 15 monographs: on the issues of pathophysiology, clinic, diagnosis and surgical treatment of congenital and acquired heart defects and major vessels, heart diseases in young children, complications after open heart surgery, surgery of complex congenital defects and coronary heart disease, heart defects with pulmonary hypertension, the use of hyperbaric oxygenation in cardiac surgery, surgical treatment of coronary disease, heart transplantation in experiment, history and philosophy of cardiac surgery. In 1970, «for the best scientific work on thoracic surgery», Vladimir Ivanovich was awarded the title of laureate of the S. I. Spasokukotsky Prize of the USSR Academy of Medical Sciences (together with B. A. Konstantinov). Academician Vladimir Ivanovich Burakovsky died on September 22, 1994 in Moscow and was buried at the Kuntsevo cemetery. The Institute of cardiac Surgery of the Federal State Budgetary Institution «A.N. Bakulev National Medical Research center of cardiovascular Surgery» (A. N. Bakulev NMRcVS) of the Ministry of Health of the Russian Federation bears his name, in which a bust of his creator is installed.